PENYELENGGARAAN PENDIDIKAN AGAMA KATOLIK DI INDONESIA - Jelahu, Timotius Tote; Prayitno, Anselmus Joko; Wuringningsih, Fransisca Romana (Bahasa Indonesia, 2023)
This article reviews Catholic Religious Education in Schools. Two things raised in this article are the formal basis in Catholic Religious Education in schools. This study uses a qualitative approach to produce descriptive data with data sources including government regulations, Church documents, and relevant previous studies. There are three conclusions from this article. First, Catholic Religious Education in schools has a constitutional basis and should be in line with the goals of National Education. First, Catholic Religious Education in schools has a constitutional basis and must be in line with the goals of National Education. Third, the performance of Catholic Religious Education in Schools is a collaboration between the Church and the Goverment. Third, the performance of Catholic Religious Education in Schools is a collaboration between the Church and the Goverment.